1998
DOI: 10.1002/j.2161-0045.1998.tb00697.x
|View full text |Cite
|
Sign up to set email alerts
|

An Anti‐Introspectivist View of Career Decision Making

Abstract: This article reviews 50 years of empirical literature on career decision making, summarizing 10 things the field knows "for sure." An anti-introspectivist view of career decision making is then presented, developed by applying findings from cognitive and experimental social psychology to career decision making. This view holds that most processing performed by the human mind for decision making and behavior initiation is not performed at a conscious level and that reflection on those processes may be futile, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 83 publications
(82 reference statements)
4
49
0
10
Order By: Relevance
“…Their ability to narrate their stories and draw upon them in times of indecision will help them deal with transitions as and when they occur. The study confirmed Krieshok's (1998) view that decision making is not simply a linear, rational process but, rather, a complex process often involving subconscious motivations. The findings also reveal that career indecision may be brought about by (conscious and subconscious) emotional problems (Di Fabio and Kenny 2011;Fouad et al 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Their ability to narrate their stories and draw upon them in times of indecision will help them deal with transitions as and when they occur. The study confirmed Krieshok's (1998) view that decision making is not simply a linear, rational process but, rather, a complex process often involving subconscious motivations. The findings also reveal that career indecision may be brought about by (conscious and subconscious) emotional problems (Di Fabio and Kenny 2011;Fouad et al 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Krieshok (1998) too argued that systematic decision making was not possible in careers. In contrast to the assumption of rational models that people could access salient aspects of self-knowledge on which to base their decision, Krieshok argued that this information is not necessarily available to individuals and decision making can be partially unconscious.…”
Section: Other-than-rational Perspectives On Career Decision Makingmentioning
confidence: 99%
“…Defining contexts may influence action directly: In the data above, Anne undertook further study to recover from being disappointed in a job application. The framework recognizes such non-career-directed actions as planless behavior, and further that action may not have conscious precedents (Krieshok, 1998). The interactive model suggests that actions may shape subsequent cognitions.…”
Section: Career Decision Making 15mentioning
confidence: 99%
“…Holland apud Martins (1978) Auto-eficácia Lent;Brown e Hackett (1994) Bandura (1977 Autoconceito/Maturidade Super (1969) Religião Lips-Wiersna (2002) Howard e Howard (1997) Constantine et al (2006) Greely (1973) Gênero Krieshok (1998) Davis (1968) Santos e Melo-Silva (2005) Super ( Status Socioeconômico Krieshok (1998) Bain e Anderson (1974) Afonso e Taveira (2001) Pavalko ( Família Levine (1976) Bohoslavsky (1987 Soares ( (2003) Leserman (1981) Roe apud Martins (1978) Etnia ou Raça Krieshok (1998) Pavalko (1988 Levine (1976) Escola Levine (1976) Astin (1968) Primi et al (2000 Figura 3 -Fatores que influenciam a escolha vocacional Interesse, valores e oportunidades Ginzberg et al (1951) …”
Section: Personalidadeunclassified
“…De acordo com a literatura, o gênero influencia tanto a escolha vocacional (KRIESHOK, 1998;TRUSTY et al, 2000) quanto o processo de socialização profissional dos estudantes de enfermagem (WAUGAMAN; LOHREN, 2000). Verificou-se, que para o sexo masculino, a escolha inconsistente faz com que haja menos socialização do que para as mulheres, fato que pode estar relacionado aos estereótipos da profissão, já que, historicamente, a enfermagem é uma profissão feminina (MUFF, 1988).…”
Section: Fator De Teste: Gênerounclassified